Significant reduction in positive surgical margin rate after laparoscopic radical prostatectomy by application of the modified surgical margin recommendations of the 2009 International Society of Urological Pathology consensus. (19th March 2016) - Maxeiner, Andreas; Magheli, Ahmed; Jöhrens, Korinna; Kilic, Ergin; Braun, Tom Lukas; Kempkensteffen, Carsten; Hinz, Stefan; Stephan, Carsten; Miller, Kurt; Busch, Jonas
Abstract : Objectives: To verify retrospectively the margin status and analyse the location and characteristics of positive surgical margins (PSMs) in patients undergoing radical prostatectomy (RP), by a central pathology review, based on the consensus conference 2009 updated margin criteria from the International Society of Urological Pathology (ISUP). Patients and Methods: The detailed PSM characteristics of 441 patients who underwent laparoscopic RP (LRP) between 1999 and 2007 were centrally reviewed with regard to location, number, Gleason score at the PSM and tumour width. Predictors of PSMs and the impact of several PSM characteristics on clinical outcomes were examined. Patient characteristics were compared using the chi‐squared test. Differences in recurrence‐free survival (RFS) rates were analysed using the log‐rank test and presented as Kaplan–Meier survival curves. Univariable and multivariable Cox regression analysis for the prediction of RFS was performed. Results: Central pathology review using the updated PSM definition according to ISUP 2009, resulted in reclassification of a substantial number of patients with PSMs ( n = 113, 26.6%) as R0. Several PSM characteristics with a higher risk of biochemical recurrence (BCR) were identified as the strongest independent predictors of RFS: pathological stage; Gleason score; and the presence of multiple PSMs (hazard ratio [HR] 1.78; 95% confidence interval [CI] 1.08–2.96; P = 0.025). Further analysis replacing the location of PSM by the width categories of PSM showed that a PSM >3 mm was an independent predictor of RFS (HR 1.72; 95% CI 1.08–2.72; P = 0.022). Conclusions: The impact of PSMs after LRP for prostate cancer remains unclear. PSMs in the present cohort of patients undergoing LRP had different characteristics and conferred different risks of BCR. A better understanding of PSM characteristics and a careful standardized pathological evaluation is needed to adequately counsel patients with respect to prognosis and adjuvant therapy after LRP.